Single-stage repair of aortic arch hypoplasia and ventricular septal defect in a low-weight infant: a case report from a resource-limited center - García Pinzás, Jesús (2025)
Aortic arch hypoplasia associated with ventricular septal defect (VSD) is a life-threatening congenital condition that demands early intervention. In low-resource settings, the lack of advanced tools complicates the safe use of selective antegrade cerebral perfusion (SACP) and innovative repair techniques such as interdigitating patch reconstruction. We describe the case of a newborn with severe aortic arch hypoplasia and a large perimembranous VSD who underwent successful one-stage surgical correction. The repair included aortic arch reconstruction using an interdigitating bovine pericardial patch and VSD closure under SACP delivered via direct brachiocephalic trunk cannulation. Despite the challenges of limited monitoring and equipment, the infant had an excellent clinical outcome. This case highlights the feasibility of adapting high-complexity cardiac techniques in resource-limited environments when surgical fundamentals and teamwork are prioritized. With strategic planning, multidisciplinary coordination, and adherence to evidence-based principles, successful single-stage repair of complex congenital heart disease is achievable even in under-resourced settings.